Małżeństwo przymierzem miłości i miłosierdzia - Rychlicki, Czesław (Ius Matrimoniale, 2016)
This article draws attention to two important values that are related to marriage. The first of them is love, which is a feature of marriage, and which is oriented on bearing and raising offspring who require responsible parenthood. The second is mercy, which is a prerequisite in marriage itself and a duty of the Church in its pastoral care of marriages facing difficulties which weaken their love and break their sacramental unity. These two values: love and mercy, considered in the context of sacramental marriage, are in a significant relation to covenant between God and human being and in relation to the covenant between Christ and the Church. Comparing these two God’s covenants with human being in the Old and New Testament with sacramental marriage leads to a clear conclusion that marriage seems as truly reflecting the covenant between Christ and the Church (cf. Ephesians 5, 21-33). In this part marriage is considered as good and sacred gift of God given to humans both for their best interests of one another and for social good. For marriage itself is a significant source of family which, in turn, is the fundamental unit of the society and nation. Since family finds its source in conjugal unity the care of Church and the state should be directed at the good of marriage and family. Such care should be displayed especially in situations in which the unity of marriage is endangered and which may lead to family breakdown.